Análise da Conformidade e Caracterização da Matéria- Prima Empregada na Fabricação de Blocos Cerâmicos na Região Metropolitana de Salvador - Couvignou, Eliana Macêdo (2007)
The potential market of the metropolitan area of Salvador accounts for the estimated consumption of roughly 800 million horizontally perforated extruded clay bricks a year. The growing demand of consumers along with the competitiveness of the structural ceramic sector has driven forward a number of recent efforts and investments towards improving the quality of structural ceramics. In this scenario, the present study focused on sampling and evaluating the conformity of 8-hole horizontally perforated extruded clay bricks manufactured by different plants (A, B and C) in the metropolitan area of Salvador. In addition, representative clay and sandy-clay materials were collected from each plant and characterized by conventional physical, chemical and mineralogical techniques. Finally, experimental compositions designated as A, B and C, according to the source, were prepared by mixing different contents of the raw materials collected in the plants, fired at different temperatures and characterized. The results revealed a series of non conformities regarding ABNT guidelines. The characterization of raw materials revealed the presence of kaolinite and ilite in concentrations ranging from 64 to 90 wt.% along with free quartz (10 - 25%). The sandy-clay samples consisted basically of kaolinite. All raw materials depicted low contents of organics, amorphous constituents, alkaline oxides and feldspar. An analysis of the firing behavior of all different ceramic compositions revealed that the linear contraction of composition A was rather significant considering the temperature range evaluated, and it justifies the significant dimensional non conformity that was shown by bricks made with the ceramic A